Strategi Digitalisasi Marketing untuk Peningkatan Pendapatan UMKM Kuliner di Desa Kajhu Kecamatan Baitussalam Kabupaten Aceh Besar - Nasron, Riwanul; Ariyanto, Agus; Maizi, Zahrul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The purpose of this community service activity is to help culinary MSME actors in utilizing digital technology to increase their marketing and income. Through training and mentoring, we identified various challenges faced by MSMEs in product marketing, including limited access to digital platforms and lack of understanding of online marketing strategies. The methods applied include training in the use of social media, creating engaging content, and digital promotion techniques. The results of this activity show an increase in MSME actors' understanding of the importance of digitalization, as well as an increase in interaction with customers by 50% through digital platforms. With the implementation of the strategy taught, the income of culinary MSMEs in Kajhu Village increased significantly from a turnover of Rp. 150,000 to an average of Rp. 250,000 per day. This activity makes a positive contribution to local economic empowerment and becomes a model for similar service programs in other regions.